The Brokenness of Caesar's Things: On the Unfinished Religious Novel by Zelda Fitzgerald - Kim, Sharon (Christianity & literature, 2019)
Caesar's Things is a semi-autobiographical novel combining modernist literary experimentation with narrative structures derived from the Bible. This unfinished work is seldom analyzed by literary scholars, in part because Fitzgerald's Christian conversion in the 1930s coincided with a mental breakdown, which made her faith and writing both suspect. Criticized as "incoherent," the novel nonetheless becomes legible when Fitzgerald's religion is disentangled from madness and its contributions examined. The novel confesses the spiritual impoverishment of the Jazz Age protagonist, then seeks her redemption, healing the divide between the self and her soul, between the material world and the kingdom of God.